2019
DOI: 10.3122/jabfm.2019.04.180380
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Defined Visit Priorities in Primary Care: Psychosocial Versus Medically-Related Concerns

Abstract: Background: Primary care providers (PCPs) are often challenged to address multiple patient concerns during time-limited visits. The need for PCPs to limit the number of issues addressed may have a negative impact on discussion of patient-defined visit priorities. Methods: Using data from a recent clinical trial (Aligning Patients and Providers, ClinicalTrials.gov: NCT02707146), we examined the association between patient-defined visit priorities and subsequent provider actions taken during and after the visit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…Consistent with previous investigations, those who smoked [20], were obese [20], and visited physicians annually [73] were more likely to report a lifetime diagnosis of anxiety disorders. There are many potential mechanisms which link obesity and anxiety.…”
Section: Research Question 4: What Other Factors Are Significantly Assupporting
confidence: 83%
“…Consistent with previous investigations, those who smoked [20], were obese [20], and visited physicians annually [73] were more likely to report a lifetime diagnosis of anxiety disorders. There are many potential mechanisms which link obesity and anxiety.…”
Section: Research Question 4: What Other Factors Are Significantly Assupporting
confidence: 83%
“…The undocumented problems mostly fall within the psychosocial domain, which has shown to have low documentation in other primary care record studies. 2,18,19 Non-documentation of problems can reflect the medicalisation of the electronic health record and the lack of a nursing lens. One reflection, which the nurses in this study had, was that they felt cautious in documenting items such as spirituality or whakapapa (Māori geneology) when they knew that the notes would be viewed by a doctor from outside the organisation, and that feedback that the nurses had received from external doctors was that they only wanted to receive 'short, sharp notes that related to medical problems'.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, observational studies were the most common (42), such as crosssectional studies and prospective studies, followed by experimental studies (12), such as (cluster) randomised controlled trials (RCTs). Descriptive studies were also included, such as narrative/literature reviews (4). No qualitative studies were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Since general practitioners (GPs) are usually the first point of contact for people with any health-related concern, patients visit their GP not only for medical reasons but also for psychosocial problems (PSPs) (1)(2)(3)(4). Here we take problems to be "a source of perplexity, distress, or vexation", while we take PSPs to refer to problems related to the conditions in which people are born, grow, live, work, and age (5).…”
Section: Introductionmentioning
confidence: 99%